IoT for Efficient Data Collection from Real World Resources - Costa, Pedro Miguel Machado Monteiro (2017)
The Internet of Things is providing new ways of experiencing and reacting to the physical world through the ability of advanced electronic devices that collect data. At the same time, as new application scenarios are envisioned, with the assistance of information generated by sensors, new problems and obstacles will arise. This requires new development to meet business and technical requirements, such as interoperability between heterogeneous devices and confidence (such as validity, security and trust) over smart devices. With the increase of these complex requirements it becomes crucial to develop an infrastructure aimed at tackling such requirements mentioned. IoT middleware – a software layer that bridges the gap between devices and information systems. Thus, this work aims to study the mechanisms and methodology for data collection, devices interoperability and data filtering, closer to the data sources, in order to optimize the collection and pre-analysis of data that can then be used by various applications such as the ones in manufacturing industry.